2020
DOI: 10.21203/rs.3.rs-57340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal Protection with PBO-Pyrethroid Synergist Treated Nets After Two Years of Household Use Against Pyrethroid-Resistant Anopheles in Tanzania

Abstract: Background: The spread of pyrethroid resistance in malaria vectors threatens the effectiveness of standard long-lasting insecticidal nets (LLIN). Synergist nets combine pyrethroid (Py) and piperonyl-butoxide (PBO) to enhance potency against resistance mediated by mono-oxygenase mechanisms. Our project assessed personal protection of WHO first-in-class PBO-Py treated nets (Olyset Plus) versus standard LLIN (Olyset net) against pyrethroid resistant Anopheles gambiae and An. funestus in North West Tanzania after … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Enhancing the bottom part might remedy nets from early hole development and further enlargement, although other studies have shown that dense knitting in this part of the net did not necessarily make it more durable. 33 Similarities in physical properties ( bers, denier, and integrity) between some nets [Chlorfenapyr-PY LLIN and PY-LLIN], but differences in protective e cacy against malaria infection emphasize the pivotal role of non-pyrethroid insecticide and synergists (chlorfenapyr and PBO 34 ) in malaria vector control. In addition, this study demonstrates that the resilient physical integrity of the nets on its own is not enough to provide sustained protection to users of intact (physically durable but insecticide-free) nets against bites of malaria-transmitting mosquitoes even in settings of high net coverage, as it was in the cohort children where we observed > 80% use.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the bottom part might remedy nets from early hole development and further enlargement, although other studies have shown that dense knitting in this part of the net did not necessarily make it more durable. 33 Similarities in physical properties ( bers, denier, and integrity) between some nets [Chlorfenapyr-PY LLIN and PY-LLIN], but differences in protective e cacy against malaria infection emphasize the pivotal role of non-pyrethroid insecticide and synergists (chlorfenapyr and PBO 34 ) in malaria vector control. In addition, this study demonstrates that the resilient physical integrity of the nets on its own is not enough to provide sustained protection to users of intact (physically durable but insecticide-free) nets against bites of malaria-transmitting mosquitoes even in settings of high net coverage, as it was in the cohort children where we observed > 80% use.…”
Section: Discussionmentioning
confidence: 99%